Capacitor‐voltage regulation and linear‐range extension of a hybrid cascaded modular multilevel converter. Issue 18 (13th November 2017) - Shi, Xianghua; Howell, Steven; Shumski, Curtis; Filizadeh, Shaahin; Jacobson, David
Abstract : This research presents a study of the hybrid cascaded modular multilevel converter. It shows that voltage regulation of the full‐bridge submodules requires special provisions for energy‐flow control between the converter's main power stage and the external ac network. Novel control and hardware methods for regulating the converter's submodule voltage and extending its linear operating range are presented. The mathematical foundations of these methods are developed using simplified converter models. Experimental results using a laboratory prototype are presented to verify the efficacy of these methods. Extensive electromagnetic transient simulation studies are also conducted to verify the proposed solutions' effectiveness in normal operating conditions as well as under dc faults.